FAMILIAL MIDFACIAL HYPOPLASIA WITH CONGENITAL HYPOPITUITARISM – A CASE REPORT - Ong, Jia Cheng; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Congenital hypopituitarism is defined as deficiency of one or more pituitary hormones due to abnormal pituitary gland development. Manifestations can be nonspecific such as poor weight gain, short stature, hypoglycemia or they may be associated with midline defects. CASE A 10-year-6-month-old female was diagnosed with congenital hypopituitarism at the age of 5 years whereby she presented with septicemic shock secondary to bronchopneumonia with hypernatremic dehydration. Detailed physical examinations showed that she was dysmorphic with short stature, poor muscle bulk, global developmental delay and features of midfacial hypoplasia such as right cleft lip/palate and septo-optic dysplasia. Investigations of the pituitary hormones revealed hypothyroidism, hypocortisolism, growth hormone deficiency and diabetes insipidus. Cranial MRI showed hypoplastic corpus callosum, absent septum pellucidum and thickened pituitary stalk with absence of bright spots of the posterior pituitary. She was started on pituitary hormone replacement including L-thyroxine, oral desmopressin, oral hydrocortisone and somatotropic injection. Clinical response to treatment was satisfactory in which she had gained 6 cm of height for the past year with normalized thyroid hormone and cortisol levels. Analyzing her family history, we noticed that her mother also had features of midfacial hypoplasia. Her elder sister is having a learning disability attending special school. This raised the possibility of genetic mutation in familial congenital hypopituitarism such as PROP1 gene. Even with similar mutation, individuals can have different levels of hormone deficiencies and be affected differently. CONCLUSION Careful evaluation of a dysmorphic child with features of midfacial hypoplasia is crucial to avoid missing congenital hypopituitarism. Early identification with comprehensive hormonal work-up is important to initiate hormonal therapy.